MKS1 regulates ciliary INPP5E levels in Joubert syndrome. Issue 1 (21st October 2015) - Slaats, Gisela G; Isabella, Christine R; Kroes, Hester Y; Dempsey, Jennifer C; Gremmels, Hendrik; Monroe, Glen R; Phelps, Ian G; Duran, Karen J; Adkins, Jonathan; Kumar, Sairam A; Knutzen, Dana M; Knoers, Nine V; et al.
Abstract : Background: Joubert syndrome (JS) is a recessive ciliopathy characterised by a distinctive brain malformation 'the molar tooth sign'. Mutations in >27 genes cause JS, and mutations in 12 of these genes also cause Meckel-Gruber syndrome (MKS). The goals of this work are to describe the clinical features of MKS1 -related JS and determine whether disease causing MKS1 mutations affect cellular phenotypes such as cilium number, length and protein content as potential mechanisms underlying JS. Methods: We measured cilium number, length and protein content (ARL13B and INPP5E) by immunofluorescence in fibroblasts from individuals with MKS1 -related JS and in a three-dimensional (3D) spheroid rescue assay to test the effects of disease-related MKS1 mutations. Results: We report MKS1 mutations (eight of them previously unreported) in nine individuals with JS. A minority of the individuals with MKS1 -related JS have MKS features. In contrast to the truncating mutations associated with MKS, all of the individuals with MKS1 -related JS carry ≥1 non-truncating mutation. Fibroblasts from individuals with MKS1 -related JS make normal or fewer cilia than control fibroblasts, their cilia are more variable in length than controls, and show decreased ciliary ARL13B and INPP5E. Additionally, MKS1 mutant alleles have similar effects in 3D spheroids. Conclusions: MKS1 functions in the transition zone at the base of the cilium to regulate ciliary INPP5E content, through an ARL13B-dependent mechanism. Mutations in INPP5E also cause JS, so our findings in patient fibroblasts support the notion that loss of INPP5E function, due to either mutation or mislocalisation, is a key mechanism underlying JS, downstream of MKS1 and ARL13B.